Production Potential of Some Agricultural Crops Under Different Spacings of Poplar - Nandal, D.P.S.; Hooda, M.S. (Indian Journal of Agroforestry, 2020)
The experiment was conducted at Forestry Research Area of CCS HAU, Hisar durinq 1995-2002 on performance of agricultural crops viz., Sorghum (Sorghum bicolor), Cowpea (Vigna unguiculata), Dhaincha (Sesbania aculeata), Moongbean (Phaseolus radiatus), Groundnut (Arachis hypogaea), Turmeric (Curcuma longa), Wheat (Triticum aestivum), Oats (Avena sativa), Berseem (Trifolium alexandrinum), Lentil (Lens esculenta) and Potato (Solanum tuberosum) for seven consecutive years under poplar plantation. In the present study, three poplar spacings (5 x 4 m, 10 x 2.5 m, 15 x 2.5 m) were tested to find out the suitable spacing for getting optimum growth and yield of interspaced crops. Results showed that yield of all crops decreased with increasing age of poplar. The yield of all crops increased with increasing poplar spacing, however, a spacing of 10 m x 2.5 m seems to be the ideal for getting optimum growth and yield of agricultural crops. The yield reduction of crops was higher during the rainy season than winter season. Agricultural crops showed variable performance both during rainy as well as winter seasons. During the rainy season turmeric gave maximum relative yield. Among other rainy season crops, cowpea for fodder was found most compatible with poplar. During the winter season, both berseem and wheat were equally compatible with poplar at all the spacings, however, at later stages of poplar growth, berseem was more tolerant to the influences of poplar than wheat particularly at closer spacing of 5 x 4 m. Lentil also proved promising for poplar based agroforestry system.